Emotions and the spatialisation of social relations in text‐based computer‐mediated communication. (18th July 2013) - Baralou, Evangelia; McInnes, Peter
<x xml:space="preserve">Abstract</x> This paper advances our knowledge of emotions in virtual teams using text‐based computer‐mediated communication. The literature's preoccupation with the absence of physical cues of emotion has meant we lack both an understanding of how emotions are co‐constructed through interaction and an explanation of their role in the social relations of virtual teams. Adopting a communicative view of emotion, we present the findings of a longitudinal study of a virtual team within a transnational collaborative project. We present three aspects of interaction that demonstrate how team members' experience and understanding of the emotions expressed through, and suppressed from, text‐based messages are influenced by the styles and patterns of interaction enabled by technology. Where our three aspects tend towards stasis, we argue that emotion provides a temporal dimension to a process of 'spatialising' social relations by connoting what should change, or what should endure, between people.